Petrogenesis of the Neoproterozoic rocks of Megele area, Asosa, Western Ethiopia - Oljira, Temesgen; Okunlola , Olugbenga Akindeji; Olatunji , Akinade Shadrach; Ayalew, Dereje; Bedada, Bekele Ayele (Earth Sciences Research Journal, 2022)
The Western Ethiopian Shield is underlain by volcano-sedimentary terranes, gneissic terranes, and ophiolitic rocks intruded by different granitoid bodies. The Megele area is part of Western Ethiopian Shield and consist of a low-grade volcano-sedimentary zone that has been intruded by mafic (dolerite dyke) and granitoid intrusions (granodiorite, diorite, granite gneiss). To establish the origin of the distinctive lithologies of the locality and evaluate its mineral potential, petrological, petrographical, and geochemical characterization of these rocks were carried out. Hence, the lithological, geochemical, and petrogenetic features of the Neoproterozoic granitoid intrusives and associated metavolcanic, were illustrated through a combination of field mapping, petrological, and geochemical analysis. The petrological result obtained from the thin section analysis of the granitoids and metabasalt from Megele area indicates that, these rocks has been metamorphosed from lower green-schist facies to lower amphibolite facies as denoted by mineral assemblages such as albite + muscovite + prehnite+ quartz and actinolite + hornblende + epidote + garnet. The major and trace element geochemical analysis of granodiorite, diorite, and granite gneiss revealed that the rocks in the studied area were mainly calc-alkaline and peraluminous in nature in the SiO2 versus Na2O+K2O and A/NK versus A/CNK, the details of the results on the major and rare elements are stated in the result section respectively. The granitoids are S-type granites revealed silica saturated rock formed at the volcanic arc subduction (VAG) to syn-collisional (syn-COLD) tectonic setting by fractionation of LREE-enriched, HREE-depleted basaltic magma with considerable crustal input. This basaltic magma seems to be generated from the LREE-enriched, HREE-depleted mantle. In conclusion, the metabasalt is sub-alkaline (tholeiitic), metaluminous bodies generated at mid-oceanic ridge tectonic setting by partially melting of HREE-depleted and LREE-enriched basaltic magma. The magma sources are associated with the reworked sediment-laden crustal slabs from the subduction zone and resulted in S-type granitoid.